Whatever happened to the family? England's new gang strategy. Issue 1 (9th January 2017) - Pitts, John
Abstract : Purpose: The purpose of this paper is to analyse the evolution ofHM government's gang strategy from 2011 to the present. It considers why an initial emphasis upon the "troubled family" as the progenitor of gang violence has given way to more tightly focussed modes of intervention in which concerns about gang violence are conflated with other policy concerns. Design/methodology/approach: The paper draws on a range of policy documents over the relevant period to demonstrate a shift in rhetoric and focus and assesses this trajectory against the evidence base suggested by other relevant literature. Findings: The argument contained in the paper attributes this shift in focus to a combination of the insights provided by new research, dwindling budgets and the reformulation of the original policy objectives in terms of recent policy priorities. Social implications: It is suggested that in times of austerity, policy initiatives are reformulated to fit available resources but changes are presented as an improvement on what went before. Originality/value: The paper uses secondary sources to develop and original analysis and argument.